Study of lattice QCD at finite chemical potential using the canonical ensemble approach - Bornyakov V. G.; Boyda D. L.; Goy V. A.; Molochkov A. V.; Nakamura Atsushi; Nikolaev A. A.; Zakharov V. I. (EPJ Web of Conferences, 2017)
A new approach to the computation of the canonical partition functions in Nf = 2 lattice QCD is presented. The results for the number density as function of imaginary chemical potential obtained in the confining and deconfining phases are used to determine the phase transition line at real chemical potential.